2007
DOI: 10.1097/01.rlu.0000255026.52044.85
|View full text |Cite
|
Sign up to set email alerts
|

Kohler Disease: Diagnoses and Assessment by Bone Scintigraphy

Abstract: Limping is a frequent occurrence in children and may be caused by various conditions, including trauma, inflammation, infection, and malignancy. Nontraumatic avascular necrosis of the tarsal bones should be included in the differential diagnosis. Accumulated data have supported the superiority of bone scans to radiography in the early diagnosis of avascular necrosis. Bone scintigraphy is a useful tool for investigating pain when symptoms, laboratory examinations, and radiography do not point to a specific diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Occurring around 2 to 3 years of age and typically 1 year earlier in girls than boys, the navicular is the last of the tarsal bones to ossify. 59 As the navicular plays an important role in the stress distribution of weight bearing, a nonossified navicular may be unduly compressed between the ossified talus and cuneiforms. This increased mechanical pressure is thought to decrease the navicular’s blood supply, resulting in ischemia, and cause necrosis within the bone’s ossification center.…”
Section: Kohler’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Occurring around 2 to 3 years of age and typically 1 year earlier in girls than boys, the navicular is the last of the tarsal bones to ossify. 59 As the navicular plays an important role in the stress distribution of weight bearing, a nonossified navicular may be unduly compressed between the ossified talus and cuneiforms. This increased mechanical pressure is thought to decrease the navicular’s blood supply, resulting in ischemia, and cause necrosis within the bone’s ossification center.…”
Section: Kohler’s Diseasementioning
confidence: 99%
“…In addition, studies focused on Kohler’s disease have suggested that poor nutrition or endocrinopathy can delay ossification of the navicular and further predispose to disease. 59…”
Section: Kohler’s Diseasementioning
confidence: 99%
“…X-rays alone may confirm the diagnosis, rendering blood tests unnecessary. Although not often required, radioisotope scans show decreased uptake on the affected side,4 and MRI demonstrates an oedematous pattern within the navicular bone 2. The prognosis is excellent owing to the navicular's radial arrangement of blood supply 1.…”
mentioning
confidence: 99%